The denationalization and agencification of net neutrality policy in Lithuania - Jastramskis, Deimantas (Array, 2019)
This paper focuses on the making of communications policy in Lithuania, specifically regarding net neutrality. The study employs a multiple stream model to analyze the conditions of the political process and the activity of political actors. The paper claims that the Lithuanian communications policy has become essentially denationalized since the country’s accession to the European Union. The issue of net neutrality policy has been framed in the context of EU policy, while the national agenda of net neutrality policy lost its significance. The denationalization of the net neutrality policy-making was harmonized with the agencification of policy formulation stage.